1970
DOI: 10.1136/bmj.4.5728.142
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Oral Contraceptives

Abstract: Summary: Of 261 women who completed a self-rating scale for measuring depression, 168 were taking oral contraceptives and 93 were using physical methods of contraception. Of the group of women taking oral contraceptives 6.6% were more severely depressed than any of the control group. There was a significant variation in the depth of depression related to the day of the menstrual cycle in the control group. This association was not found in the oral contraceptive group, where premenstrual depression was limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Studies that have examined the effects of these hormone treatments on mood have predominantly been conducted in populations of women with Premenstrual Dysphoric Disorder (PMDD) or healthy women. Early studies using oral contraceptives with high progestin doses reported depression as a possible side effect in normal women in case series and small case-control studies (Nilson and Almgren, 1968;Herzberg et al, 1970;Worsley and Chang, 1978). A large epidemiological-based study found that among women with PMDD who were starting hormone-based contraceptives, most women showed no change in mood, with mood improving in some women and worsening in others (Joffee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined the effects of these hormone treatments on mood have predominantly been conducted in populations of women with Premenstrual Dysphoric Disorder (PMDD) or healthy women. Early studies using oral contraceptives with high progestin doses reported depression as a possible side effect in normal women in case series and small case-control studies (Nilson and Almgren, 1968;Herzberg et al, 1970;Worsley and Chang, 1978). A large epidemiological-based study found that among women with PMDD who were starting hormone-based contraceptives, most women showed no change in mood, with mood improving in some women and worsening in others (Joffee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is based on the findings that estrogen supplements in birth control pills may induce depressive states (Herzberg et al 1970) and that younger adults and adolescents, who presumably have higher sex hormone levels than older adults and prepubertal children, respond less favorably to antidepressants (Ryan et al 1986). However, these theories have not been substantiated with empirical data.…”
Section: Discussionmentioning
confidence: 97%
“…While some studies have shown emotional disturbances associated with hormonal contraception use, others have shown no effect or even a beneficial effect of hormonal contraception use. 29,[60][61][62][63][64] DMPA use, though, has more consistently been shown to increase risk of depression. While a retrospective study that evaluated DMPA and risk of postpartum depression found no effect, a randomized trial of a long-acting injectable progestin demonstrated increased risk of postpartum depression.…”
Section: Discussionmentioning
confidence: 99%